Defining human cardiac transcription factor hierarchies using integrated single-cell heterogeneity analysis. Issue 1 (December 2018) - Churko, Jared; Garg, Priyanka; Treutlein, Barbara; Venkatasubramanian, Meenakshi; Wu, Haodi; Lee, Jaecheol; Wessells, Quinton; Chen, Shih-Yu; Chen, Wen-Yi; Chetal, Kashish; Mantalas, Gary; Neff, Norma; et al.
Abstract Human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) have become a powerful tool for human disease modeling and therapeutic testing. However, their use remains limited by their immaturity and heterogeneity. To characterize the source of this heterogeneity, we applied complementary single-cell RNA-seq and bulk RNA-seq technologies over time during hiPSC cardiac differentiation and in the adult heart. Using integrated transcriptomic and splicing analysis, more than half a dozen distinct single-cell populations were observed, several of which were coincident at a single time-point, day 30 of differentiation. To dissect the role of distinct cardiac transcriptional regulators associated with each cell population, we systematically tested the effect of a gain or loss of three transcription factors (NR2F2, TBX5, andHEY2 ), using CRISPR genome editing and ChIP-seq, in conjunction with patch clamp, calcium imaging, and CyTOF analysis. These targets, data, and integrative genomics analysis methods provide a powerful platform for understanding in vitro cellular heterogeneity. Human induced pluripotent stem cell derived cardiomyocytes are a powerful model for cardiogenesis and disease in vitro. Here the authors comprehensively map cardiac differentiation using multiple modalities, including single-cell RNA seq and CyTOF, in cells with a gain  or loss of function in key cardiac transcription factors.